A Monolithically Integrated SiC Circuit Breaker - Boettcher, Norman; Erlbacher, Tobias (IEEE Electron Device Letters, 2021)
In this letter, a monolithically integrated SiC circuit breaker device providing self-triggered blocking operation is presented. The proposed topology is implemented into a common 4H-SiC JFET technology, which offers conventional cell design and chip scaling opportunities. Basic operation and design implications are discussed on the basis of quasi-static electrical measurements of fabricated nJFET, pJFET and circuit breaker devices. The design of experiment including a variation of channel length and channel doping dose reveals a distinct effect on the design targets, especially on on-state resistance, trigger current and blocking voltage. The investigated devices exhibit trigger current density levels of up to 2.8 A/cm2 and self-sustained blocking capability up to 795 V DC-link voltage. On-state resistance at room temperature is determined to 0.93 Ωcm2 but drastically decreases at elevated temperatures, as is shown in the experiments.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 4H-SiC; automotive; circuit breaker; Circuit breakers; DC grid; JFETs; Logic gates; monolithic integration; Resistance; self-triggered; Silicon carbide; Temperature measurement; Voltage measurement